Impact of market efficiency on share price: evidence from listed beverage and tobacco companies in sri lanka - Anushiya, A. (University of Jaffna, 2016)
Theoretically, there are numerous components which have predictable influence on share price of the company including company's performance, industry's performance, investors' sentiment and economic factors. Precisely the company's performance components include announcement on earnings, profits and dividends, and future estimated earnings . These components help to improve the market efficiency of the company. The purpose of this study is to examine the impact of market efficiency on share price and test market efficiency in Colombo Stock Exchange (CSE) by using a sample of 53events (15 companies) and earning price per share from beverage and tobacco companies listed in Colombo Stock Exchange during a period of 5 years from 2010 to 2014. A sample of 15 listed companies were randomly selected among the 23 beverage & tobacco companies listed in CSE. The market efficiency was measured using earning per share (EPS) and dividend announcement as independent variables, while the market price per share (MPS) is considered as the proxy for the share price in the study as a dependent variable. The statistical analysis including regression model is used to find out the impact of EPS on MPS as well as a standard event study method is also considered to explore whether market is efficient or not in particular period considered for the study. The result of the standard event study method shows that the market slowly responds to the price adjustments in the post announcement period to information implies that market is of informational inefficient. It can be observed through the trend of cumulative average abnormal returns (CAARs). Further, regression analysis shows that there is a positive significant impact by the earning price per share on the market price per share. Consequently, it can be concluded that the market efficiency has significant impact on the share price in the beverage and tobacco sector of Sri Lanka.
Keywords: Beverage and tobacco sector; Dividend announcement; Market efficiency; Share price